Behavior and marketing mix of selective the annual basic healthcare services with private company in the central region area - Phudamrong, Phichet (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
The purposes of this research were to (1) to study the behavior of selective the annual basic healthcare services with private company in the central region area (2) to study level of marketing mix of the behavior of selective the annual basic healthcare services with private company in the central region area (3) to study of selective the annual basic healthcare services with private company in the central region area effected the level of marketing mix and organization factors. (4) to guideline the annual basic healthcare services with private company in the central region area. The researchers used a mixed methods approach. The quantitative research of which 51,730 private company collected data of a sample size 400 using random sampling. The multi- stage random sampling up to 10 provinces including Bangkok, Nonthaburi, Pathum Thani, Samut Prakan, Samut Sonkham, Nakhon Pathom, Ayutthaya, Prachinburi, Ratchaburi and Kanchanaburi by collected the data from 40 private company. Research Tools used in questionnaires and interviews from researchers created. The Data were analyzed by frequency, percentage, and average, standard deviation, Chi-squared test Analysis, Multiple Regression Analysis and Content Analysis. The results showed that (1) Behavior and marketing mix of selective the annual basic healthcare services with private company in the central region area. Most of the frequency of use of health services per year (93.50 percent), the cost of annual basic healthcare services in the range of 500-1,000 baht (53.25 percent) and the participants in selective a health check, including a joint decision between employees and entrepreneurs (61 percent), the purpose of monitoring the health of the organization. To benefit employees (74 percent) of the healthcare services include: The annual healthcare services check of employees in the organization (75 percent) and the provider of health services, including the top three on three locate. (1) Private hospitals (77 percent) (2) the use of the marketing mix in its annual basic healthcare services with private company in the central region area. The research found that Marketing mix that influence the selection of the annual basic healthcare services with private company in the central region area, including the top three. Factors personnel (Mean = 4.28) price (Mean = 4.25) and products (Mean = 4.20), respectively (3) Factors organizations do not affect the use of health services for the annual basic healthcare services with private company in the central region area in a joint decision of both employees and entrepreneurs. And selecting a health check in as the marketing mix that influence service selection of the annual basic healthcare services with private company in the central region area. (4) Ways to selective annual basic healthcare services with private company in the central region area. In order to be successful and sustainable action on the matter. The diagnostics and service quality and to satisfy and meet the needs of establishments. Choose a provider that can meet the needs of enterprises, and can answer any questions or problems about the health of the employees or customers and to focus on the service provider that can meet the needs of enterprises and. the after sales service is good. Article history : Accepted 16 January 2017 SIMILARITY INDEX = 3.04